2010
DOI: 10.2334/josnusd.52.477
|View full text |Cite
|
Sign up to set email alerts
|

Oral geotrichosis: report of 12 cases

Abstract: Oral geotrichosis is an uncommonopportunistic infection caused by Geotrichum candidum, a habitual contaminant and component of the flora of various parts of the body. This communication reports both a 20-year retrospective study of clinically and mycologically proven cases of oral geotrichosis, and a prospective study of fungal oral flora in 200 individuals divided into two groups: normal individuals and individuals with associated conditions. Twelve patients with proven oral geotrichosis were included: 9 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 16 publications
1
52
0
1
Order By: Relevance
“…Amphotericin B is indicated for the treatment of deep lesions. In vitro studies have reported a good spectrum with voriconazole; in clinical case studies, the results have varied .…”
Section: Geotrichosismentioning
confidence: 99%
“…Amphotericin B is indicated for the treatment of deep lesions. In vitro studies have reported a good spectrum with voriconazole; in clinical case studies, the results have varied .…”
Section: Geotrichosismentioning
confidence: 99%
“…Species of these arthroconidium-forming genera are important, although rare, human pathogens. In healthy humans, they persist as colonizers of the gastrointestinal tract, the oral cavity and respiratory tract, skin, and hair (3,4). Their clinical relevance should not be neglected, as bloodstream infections caused by species of Trichosporon and Geotrichum may occur among cancer patients and immunocompromised individuals (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Though rare, various Geotrichum species are found to affect the respiratory tract, skin, oral cavity and also invasive infections, in the immunocompromised host. [8] Probably, this is the first report on the isolation of G. candidum from Indian HIV seropositive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…[3456] Furthermore, there are other yeasts, previously thought to be nonpathogenic, now gaining importance, especially in the era of HIV/AIDS. [78] In the Indian scenario, only a few reports are available on asymptomatic carriage of yeasts in the oral cavity of HIV seropositive individuals. [345910] Most of these studies are, however, from the southern states of the country.…”
Section: Introductionmentioning
confidence: 99%